Mail Art : Czyli Sztuka Poczty - Folga-Januszewska, Dorota; Rypson, Piotr (Warsaw : National Museum, 1991)
Fricker, H.R. ; Bleus, Guy ; Tisma, Andrej ; Perneczky, Geza ; Petasz, Pawel
Mail Art : Czyli Sztuka Poczty, Museum Narodowe w Warszwaie / National Museum in Warsaw, April - August 1991
Pools & Engels
kunstcatalogus